Peran Dinas Pemberdayaan Perempuan Perlindungan Anak dan Keluarga Berencana dalam Implementasi Kabupaten Layak Anak di Kabupaten Aceh Barat - Hildhah, Fitriah; Hajad, Vellayati; Ikhsan, Ikhsan; Liyana, Cut Irna (Equalita: Jurnal Studi Gender dan Anak, 2025)
A Child-Friendly District is a form of mandatory government affairs that focuses on empowering women and protecting children to ensure every child gets their rights according to the Convention on Children's Rights, as regulated in West Aceh Regent Regulation Number 40 of 2018. This research aims to evaluate the role of the Women's Empowerment, Child Protection and Family Planning Service in implementing the Child-Friendly District concept in West Aceh Regency. The research method used is descriptive qualitative, with data collection techniques through observation, interviews and documentation. There were six informants for this research. The research results show that implementing the concept of a Child-Friendly District in West Aceh Regency has not been optimal. Based on Biddle and Thomas' theory, the role as a policy has been running optimally, but the role as a strategy and communication tool has not been implemented well. The main obstacles include lacking human resources, facilities, budget, and communication between organizations and activity implementers. Apart from that, the lack of outreach and communication by the Women's Empowerment, Child Protection and Family Planning Services means that the public does not fully know the status of the Child-Friendly District in West Aceh Regency. In conclusion, although there are efforts to implement a child-friendly district in West Aceh Regency, improvements are still needed in various aspects to achieve optimal implementation.